Histopathological Prognostic Factors In Carcinoma Breast - An Indian Institutional Experience - Reddy, S.Rajasekhar; Chaitanya, Balekuduru; Latha, P. Swarna (International Journal of Medical Research and Review, 2014)
Objective: Pathological prognostic factors in breast cancer are now widely used to predict biological behavior of cancer and to plan its effective management. In this paper, we attempt to evaluate the reports from our histopathology laboratory spanning over a period of 2 years. The aim of this descriptive study was to see the various histopathological features of breast cancer in order to know the pattern of disease in recent time in India. Methods: The pathology reports of primary carcinoma of the breast diagnosed in our laboratory from 1st January 2010 to 31st December 2012 (2 year period) were reviewed for details on tumor size, histological type and grade, presence or absence of tumor emboli in vascular channels and lymph node status. Results: Total of 174 patients was included in the study. The mean age of presentation was 47.84 years. In 86 cases the lump was palpable in the upper lateral quadrant, followed by 52 cases in the upper medial quadrant. Duct cell carcinoma was the most common histological subtype (148 cases) accounting for 85% of the cases. Mucinous carcinoma was the second most common, occurring in 7 cases (4%). 81.61 % of tumours were grade II. Highest number of tumours were detected in the T2 stage i.e with size varying between 2 – 5 cms (67.24%). In decreasing frequency T3 > T1 > T4 stage tumours were observed. More number of cases in our study population belonged to either N0 category or N1 category. 90 cases had lymphovascular invasion in our study accounting for 51.72%. Conclusion: Our study puts forth the trends in histopathological prognostic factors in primary carcinoma breast in India.